Efecto de la infección con Eimeria falciformis sobre el desarrollo de la Toxoplasmosis en ratón - Chinchilla C., Misael; Guerrero B., Olga Marta; Marín R., Roberto (Revista de Biología Tropical, 1986)
White mice previously infected with 102, 103 or 104 Eimeria falciformis oocysts on days 0, 5, 10 or 30 were inoculated per os with 101, 102, 103 or 104 Toxoplasma oocysts. While the results obtained for mice with higher Toxoplasma inocula were consistent, animals with 101 and 102 oocyts previous inoculation with Eimeria showed important differences related with those infected only with Toxoplasma. For example, survival time was higher in animals infected with both parasites, especially if inoculated with Eimeria 30 days before Toxoplasma infection. Furthermore the number of T. gondii cysts found in the animals previously infected with Eimeria was lower compared with mice inoculated with Toxoplasma only. Body weight of mice infected with Toxoplasma previous infection with Eimeria was almost normal in relation to those infected only with Toxoplasma, indicating a probable pathological effect due to the parasite, more evident in "non immunized" mice.